Answer:
(or 6.25)
Step-by-step explanation:
Let's do a simple square problem to see the relationship between the elements of the resulting equation...
![(x+3)(x+3) = x(x+3) + 3(x+3) = x^{2} +3x + 3x + 9 = x^{2} + 6x + 9](https://tex.z-dn.net/?f=%28x%2B3%29%28x%2B3%29%20%3D%20x%28x%2B3%29%20%2B%203%28x%2B3%29%20%3D%20x%5E%7B2%7D%20%2B3x%20%2B%203x%20%2B%209%20%3D%20x%5E%7B2%7D%20%2B%206x%20%2B%209)
As you see, the number of 'x' (6) is the double of the numeric part of the binomial expression (3), while the numeric-only part (9) is the square of the numeric part of the binomial expression (3).
So, if we look at the formula from the problem, we see the the number of 'x' is 5. To obtain the C value, we need to divide the 5 by 2... then get the square value of the result.
(or 6.25)
Answer:
The first pair.
Step-by-step explanation:
3 corresponding parts must be congruent for two triangles to be congruent. The first pair has 3 congruence markings; two angles and one side are congruent. Additionally, they are congruent by the ASA postulate because two angles and the included side are congruent.
Answer:
three to five or three over five that one is like division
Step-by-step explanation:
The value of ∠X = 58.11°, If ΔWXY, the measure of ∠Y=90°, XW = 53, YX = 28, and WY = 45.
Step-by-step explanation:
The given is,
In ΔWXY, ∠Y=90°
XW = 53
YX = 28
WY = 45
Step:1
Ref the attachment,
Given triangle XWY is right angled triangle.
Trigonometric ratio's,
∅
For the given attachment, the trigonometric ratio becomes,
∅
.....................................(1)
Let, ∠X = ∅
Where, XY = 28
XW = 53
Equation (1) becomes,
∅ ![= \frac{28}{53}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B28%7D%7B53%7D)
∅ = 0.5283
∅ =
(0.5283)
∅ = 58.109°
Result:
The value of ∠X = 58.11°, If ΔWXY, the measure of ∠Y=90°, XW = 53, YX = 28, and WY = 45.